Sustainable utilisation of oil palm empty fruit bunch and perenniporia subtephropora for eco-friendly mycelium-based biofoam - Mohd Izan, Nur Liyana; Kamal Bahrin, Ezyana; Mohd Yusoff, Mohd Zulkhairi; Simarani, Khanom; Sharip, Nur Sharmila; Ariffin, Hidayah (Elsevier, 2024)
Recently known as an alternative to expanded polystyrene foam (EPS), mycelium-based biofoam (MBF) has been introduced as a new technology foam. The desired traits of MBF are currently being studied by exploring various factors that can influence the end-product. Following preliminary screening, two local fungi, Phanerochaete concrescens isolate LYN-UPM S1 and Perenniporia subtephropora isolate LYN-UPM S9, were selected based on their positive outcomes. These fungi, along with two other positive controls were cultivated on local biomass to develop MBF. The present study applied several analytical techniques to analyse and validate the attributes of the local MBF, including physical, chemical, and mechanical analyses. Perenniporia subtephropora isolate LYN-UPM S9 displayed the best results as MBF by exhibiting hydrophobic properties with 93◦ of contact angle, and 0.23 kJ/m2 impact strength. Subsequently, the characteristics of MBF and EPS have been differentiated in this study. This study not only advances the understanding of MBF characteristics but also paves the way for further exploration into optimizing mycelium-based materials for sustainable packaging solutions. Future research should focus on scaling up production, improving performance, and evaluating the environmental impact of MBF in practical applications.